The Radical Islamic Movement in Indonesia: Roots and Factors - Ansori, M. Afif (KALAM, 2019)
Radicalism has become one of the recent world problems faced by many countries, including Indonesia. The radical movement in this country is growing rapidly, especially after the reformation era. The spirit of democracy has provided opportunities for radical Islamic groups to express their beliefs openly and use religious symbols in their religious and social movements. This article aims to analyze the historical roots of radicalism in Indonesia and the factors that influence it. This article uses descriptive qualitative methods. The results of the study indicate that the radical movement in Indonesia can be traced from the tendency of groups trying to realize the Islamic State system (the khilafah) in Indonesia. This tendency can be found in several radical groups such as Darul Islam (DI/TII), Jama'ah Islamiyah, Hizb ut-Tahrir Indonesia (HTI), Laskar Jihad, Laskar Jundullah, Laskar Fisabilillah, Islamic Defender Fronts (FPI), and Preparatory Committee for the Application of Islamic Sharia (KPPSI). The study concludes that radicalism in Indonesia is the response of Muslims to the social, economic, and political conditions of Muslims in Indonesia.